Pancasila Sebagai Ideologi Negara dalam Pembangunan Demokrasi Indonesia (International Forum of Researchers and Lecturers, 2024)
Pancasila as a state ideology plays a fundamental role in the development of Indonesian democracy, but its implementation faces various challenges in the contemporary era. This research aims to deeply analyze the strategic role of Pancasila in building and strengthening the democratic system in Indonesia, focusing on the dynamics of its implementation, challenges, and strengthening strategies. Using a literature review method with a qualitative-descriptive approach, this research analyzes various literature sources from 2019-2024 through systematic literature review (SLR) and critical discourse analysis (CDA). The results show that Pancasila plays an effective role as an instrument that bridges Indonesia’s diversity with universal democratic principles, as well as a filter in the adoption of global democratic values. Implementing Pancasila values in the context of democratization requires a comprehensive approach that includes strengthening leadership, revitalizing education, and adapting to digital transformation. This research contributes to the development of a strategy to strengthen Pancasila-based democracy that is adaptable to the times, but still rooted in the noble values of the Indonesian nation.